Effect of post-mining restoration of the xerophytic scrub community, in Nuevo León, Mexico - Marroquín-Castillo, Jonathan J.; Alanís-Rodríguez, Eduardo; Jiménez-Pérez, Javier; Aguirre-Calderón, Oscar A.; Mata-Balderas, José M.; Rubio-Camacho, Ernesto A.; Collantes Chávez-Costa, Alejandro (Instituto de Ecología, A.C., 2017)
Background and Aims: Restoration strategies promote the recovery of disturbed ecosystems in order to renew their natural structure and function. Our research evaluated the abundance, dominance, frequency, and diversity of species in three areas of Tamaulipan thornscrub.Methods: Two areas were subject to opencast limestone mining over the course of seven years from 2000 to 2006. Restoration techniques were applied in one of the excavated areas, whereas this was not done in other. The third one, an undisturbed area, was used as the reference community. In 2013, we recorded ecological attributes of established plant communities in 36 preselected 100 m2 (10 m × 10 m) sampling sites, 12 per site.Key results: The area without restoration did not register regeneration within the vegetation. Species richness (S), Margalef index (DMg) and Shannon index (H’) showed significant differences (mean values S 4.75 and 8.25, DMg 0.87 and 1.80, H’ 0.7 and 1.54, respectively) between the restored and reference area while the variables of density, crown area, and Pretzsch index (A) were similar.Conclusions: Based on the similarity in the density and crown area with a reference area, we conclude that active restoration techniques, involving deposition of rock and soil materials and exclusion of industrial activities, generate favorable conditions for the reestablishment of vegetation communities in Tamaulipan thornscrub in seven years.